Comparison of follicular fluid and serum levels of Inhibin A and Inhibin B with calculated indices used as predictive markers of ovarian hyperstimulation syndrome in IVF patients - Pavelkova Jana; Filova Vanda; Moosova Martina; Rezabek Karel; Moos Jiri; Peknicova Jana (BMC, 2009)
Abstract Background Ovarian Hyperstimulation Syndrome (OHSS) is a severe health complication observed in some patients undergoing hormonal stimulation during IVF. Presence of OHSS is often associated with a high count of growing follicles responding to FSH hyperstimulation. However, the number of responding follicles may not be sufficient enough to predict the onset and severity of OHSS. The aim of this study was to find whether follicular fluid (FF) and serum concentrations of Inhibin A and Inhibin B in patients undergoing IVF treatment may serve as a predictor of OHSS status independent of the growing follicles count. Methods Serum and follicular fluid of fifty-three women undertaking the IVF program were separated into four groups according to their OHSS status and growing follicles count and analyzed for serum and FF concentrations of Inhibin A and Inhibin B. The resulting data were combined with clinical and demographic data to calculate indices independent of the growing follicles count. Results Serum Inhibin A and Inhibin B concentrations showed no significant difference between the severe OHSS group and the control group without OHSS. Moreover, the serum concentrations of Inhibin A and Inhibin B were strongly correlated with the growing follicles count. Their concentrations in the high responders group (>18 follicles) were significantly higher (p < 0.00001, p < 0.0001) when compared with normal and low responders (<18 follicles). To suppress the dependence on the growing follicle count, three indices were constructed and calculated. The best association with OHSS status and independence of the growing follicle count was achieved by using the Inhibin B TFF/SBM index calculated as follows: [concentration in FF] × [growing follicle count]/[concentration in serum] × [body mass]. The Inhibin B TFF/SBM index showed a clear difference (p = 0,00433) between the group with severe OHSS and the control group, while showing no apparent correlation with the growing follicle count. Conclusion These observations demonstrated that while neither serum nor FF concentrations of Inhibin A nor Inhibin B can be used as an OHSS predictor independent of the growing follicle count, calculated indices may meet the criteria.